Tariffs and macroeconomic dynamics - Marco Hernández Vega (Banco de México, 2021)
This paper studies the macroeconomic impact of higher tariffs using a two-country DSGE model with endogenous trade and heterogeneous firms. The analysis consists of two scenarios. First, we assume that one country increases tariffs while the other does not. Second, both countries raise tariffs. In the first case, the country that did not raise tariffs suffers an economic contraction due to lower external demand. In turn, the one that imposed higher tariffs ends with a slight gain in output triggered by a surge in internal consumption originated from the transfer of tariff revenue to households. In the second case, however, both countries suffer a significant drop in exports, reducing dividends and wages paid, and decreasing consumption and output.
Keywords: F12; F13; F17; F41; F62; 330; Endogenous Trade; Firm Heterogeneity; Firm Dynamics; Tariffs